Impact of SARS-CoV-2 Infection During Pregnancy on Infant Neurobehavioral Development: A Case-Control Study - Cheng, Yao; Teng, Haoyue; Xiao, Yue; Yao, Mengxin; Yin, Jieyun; Sun, Guoqiang (Frontiers in Pediatrics, 2021)
Background: Previous studies on the pneumonia outbreak caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have focused on the general population and pregnant women, while little is known about the effects of SARS-CoV-2 on retardation during and after pregnancy. The purpose of this study was to evaluate the potential influence of SARS-CoV-2 on infant neurobehavioral development. Methods: A case-control study was conducted in Wuhan Maternal and Child Health Hospital, China. Nine pregnant women with SARS-CoV-2 infection and 9 controls matched by maternal age, parity, and status of chronic disease were included. Infantile neurobehavioral development was assessed through the Ages and Stages Questionnaires Edition 3 (ASQ-3). Results: The majority of pregnant women with SARS-CoV-2 experienced cesarean section (7 of 9), which was higher than the control group (5 of 9). The throat swabs of all newborn were negative. We found that compared with the control group, neonates of mothers with SARS-CoV-2 infection during pregnancy had lower scores in communication, gross movement, fine movement, problem solving, and personal-social domains; but only fine movement domain yielded statistical significance (P=0.031). Conclusion: Infection with SARS-CoV-2 during pregnancy may have a certain impact on infant neurobehavioral development. Further studies with larger sample size are warranted for validation.